Doing Business Regional Profile 2016 : Middle East and North Africa - World Bank Group (World Bank, Washington, DC, 2016)
Doing Business sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 11 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency and labor market regulation. Doing Business 2016 presents the data for the labor market regulation indicators in an annex. The report does not present rankings of economies on labor market regulation indicators or include the topic in the aggregate distance to frontier score or ranking on the ease of doing business. This regional profile presents the Doing Business indicators for economies in Middle East and North Africa (MENA). It also shows the regional average, the best performance globally for each indicator and data for the following comparator regions: Latin America, East Asia and the Pacific (EAP), Europe and Central Asia (ECA), South Asia (SA) and OECD High Income.. The data in this report are current as of June 1, 2015 (except for the paying taxes indicators, which cover the period January–December 2014).